Food, nutrition and sustainability education in Australian primary schools: a cross-sectional analysis of teacher perspectives and practices - Jessica V Kempler; Claire Margerison; Janandani Nanayakkara; Alison Booth (Archives of Public Health)
Abstract Background Healthy eating patterns from sustainable food systems are crucial for population and planetary health. Primary schools are opportune settings for teaching children about food, nutrition and sustainability (FNS) though little is known about the delivery of FNS education in this sector. This study aimed to analyse current approaches to FNS education in Australian primary schools. Methods A cross-sectional online survey with closed- and open-ended questions collected data about (i) teacher perceptions and attributes regarding FNS education; (ii) FNS teaching practices; and (iii) factors influencing FNS education. Statistical analyses were conducted using STATA including descriptive statistics and chi-square analyses to test for associations between categorical variables. Qualitative content and thematic analyses of open-ended questions were conducted using NVivo 14. Results Participants were 413 Australian primary school teachers. Teachers considered FNS education as equally important to most curriculum subjects, though frequency of FNS education was low. Less than a third of teachers were trained in FNS education, had access to funding for FNS-related activities or were from schools with policies about including FNS education in the curriculum. There was a significant association between frequency of FNS education and teacher training, access to funding and presence of FNS curriculum policies (all p < 0.001). Teachers who were trained to teach nutrition, food skills or food sustainability (all p < 0.05) were more likely to teach this as both stand-alone and cross-curricular subjects. Teachers described personal factors (workload, stress, scope of practice) that influenced their FNS teaching practices, as well as factors related to students’ families (family responsibility for FNS education, family food practices, family engagement in FNS activities), the curriculum (overcrowding, prioritisation, access to resources) and the broader school environment (time, facilities, funding, training). Conclusions Strengthening the position of FNS education in the primary school sector is an important next step for public health research, policy and practice. Researchers and policy makers should explore future opportunities for training, funding and policy approaches that prioritise FNS within the primary school curriculum and in everyday teaching practice.